2012
DOI: 10.3171/2012.5.jns111611
|View full text |Cite
|
Sign up to set email alerts
|

A randomized study of urgent computed tomography–based hematoma puncture and aspiration in the emergency department and subsequent evacuation using craniectomy versus craniectomy only

Abstract: Patients with massive spontaneous supratentorial ICHs may benefit from more urgent surgical decompression. The results of logistic regression analysis implied that, to improve long-term functional outcome, decompression should be performed in patients before herniation occurs. Due to the fact that most of these patients have signs of herniation when presenting to the ED and because conventional surgical decompression requires time to take effect, this combination of surgical treatment provides a feasible and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Additionally, recent retrospective studies have suggested a possible role for craniectomy in ameliorating increased ICP caused by ICH. [230][231][232][233][234] In addition, the current recommendations do not apply to intracranial hemorrhage caused by trauma or underlying structural lesions such as aneurysms and arteriovenous malformations, because these patients were not included in the described ICH surgery trials.…”
Section: Surgical Treatment Of Ich (Clot Removal)mentioning
confidence: 99%
“…Additionally, recent retrospective studies have suggested a possible role for craniectomy in ameliorating increased ICP caused by ICH. [230][231][232][233][234] In addition, the current recommendations do not apply to intracranial hemorrhage caused by trauma or underlying structural lesions such as aneurysms and arteriovenous malformations, because these patients were not included in the described ICH surgery trials.…”
Section: Surgical Treatment Of Ich (Clot Removal)mentioning
confidence: 99%
“…However, several factors including the old age, APT, and/or comorbid burden need attentions before appropriate surgical procedures were performed. It was reported that TDC could help to prevent subsequent brain injury, assist in stabilizing the clinical condition, and improve the outcome of TBI patients, and it has been chosen for saving valuable time in the patients with TASDH before the evacuation of subdural hematoma via large craniotomy or decompressive craniectomy [1].…”
Section: Discussionmentioning
confidence: 99%
“…The mean duration of TDC in this study was 14.4 min (6-19 min). Therefore, TDC was more suitable to apply for emergency situations, and when it was combined with other surgical treatment such as subsequent craniotomy, it would provide a more safe, feasible, and effective surgical option than craniotomy only [1]. However, few reports showed that acute subdural hematomas were successfully removed with TDC alone or combined with the instillation of urokinase.…”
Section: Discussionmentioning
confidence: 99%
“…Among the survivors, improvements in GCS score of more than three points, compared to preoperative measurement, were more frequently observed among the early (less than 3 hours between trauma onset and operation) decompressed cases ( p =0.013). Similarly, Xiao et al 41) in addressing the effect of DC on long-term functional outcomes, discerned that early decompression should be performed in patients before herniation occurs. Additionally, Csókay et al 10) also reported the importance of very early DC in the aspect of ICP increase prevention in children with severe traumatic brain swelling.…”
Section: Discussionmentioning
confidence: 99%
“…The pupil diameter was measured using a millimeter ruler, and a fixed pupil was defined as a constriction of less than 1 mm when the light reflex was checked. Based on this definition, brain stem compression was defined as a pupil grade of less than 3, as categorized by Xiao et al 41) Pupil grade was categorized as either Grade 0, bilaterally fixed pupils; Grade 1, unilaterally fixed with a fixed pupil diameter >7 mm; Grade 2, unilaterally fixed with a fixed pupil ≤7 mm; Grade 3, unilaterally sluggish; Grade 4, a bilaterally brisk response; or Grade 5, normal response. The length of time between trauma onset and decompression was obtained by reviewing information recorded by the National 119 Rescue Service and operation records.…”
Section: Methodsmentioning
confidence: 99%